Produção autoral de vídeo: uma proposta de ensino com o uso de tecnologias digitais em aulas de estatística - REIS, Josiane Silva dos (Universidade Federal do Pará, 2019)
The present work investigated the video production contribution as methodological proposal for teaching of statistics, with a group os students of the 9 th grade of Elementary School from a public school. This is a qualitative research, a participative research, that aimed to develop a process of teaching with the production of a material audiovisual, and the data were analyzed in light of the interpretative analysis of Cresweell (2007). The research was carried out in two major phases: in the first, the group of participating students had the opportunity to organize knowledge and discuss the basic concepts of statistics in an online forum created in a social network; in the second, the group created strategies, organized and elaborated materials for the production and editing of the video. The work took place in the context of Collaborative Learning, which has as one of its theoretical assumptions the Interactionist Theory of Vygotsky (1989), in which knowledge can be built collectively in the exchange between peers and through interaction.Thus, the technology guides all the proposed teaching process and enables the development of a teaching proposal that can overcome the traditional proposals of knoledge reproduction. The results showed that the collaborative learning, fomented by the use of digital technologies, favored interaction and instigated the autonomous attitude of the students in the pursuit and understanding of knowledge in statistics, besides that, the strategies and applicability of the built knowledge allowed the group of students recognized a problem of their reality and seek solutions resolve it. Regarding the product of this work, I believe the video, as a result of the proposed teaching process, it allowed to consolidate the research and serves as a guidance resource for teachers seeking differentiated teaching practices with the use of digital technologies.